Solidarność . pismo MKZ NSZZ Solidarność z siedzibą w Gdańsku, no. 54, 1981 - [Międzyzakładowy Komitet Strajkowy, [Mariusz Wilk EIC] (KZ NSZZ "Solidarność", 1981)
Creation and circulation: Issues no. 15(1980)-no 32=62(1981) and from issue no. 19[i.e.17]=232(1989) published legally. Afther the introduction of the Martial Law published underground, with numeration continous with the 1980-1981 publication